Research into New Molecules with Anti-Inflammatory Activity - Abel Vale; Mariana Lucas; Daniela Ribeiro; Eduarda Fernandes (Medical Sciences Forum, 2023)
The drugs currently available as cyclooxygenase-2 (COX-2) inhibitors increase the risk of cardiovascular events, which justifies the search for new alternative anti-inflammatory molecules. This work aimed to evaluate the anti-inflammatory activity of the chalcones (polyhydroxylated aromatic compounds): 2′,3,4,4′,6′-pentahydroxychalcone (5OH), 2′,3,4,4′,6′-pentamethoxychalcone (5OMe), and 2′,3,4,4′-tetrahydroxychalcone (butein), at non-cytotoxic concentrations, in an experimental human whole blood model. The results obtained showed that none of the chalcones under study was cytotoxic to human blood cells. From the tested chalcones, butein was the only one showing a concentration-dependent inhibitory production of prostaglandin E2, via COX-2, in human blood (40 ± 8%, at 50 µM).